Perbandingan Efektifitas Penggunaan Media Pembelajaran Audio Visual dan Teks Untuk Meningkatkan Pemahaman Isi Dongeng Siswa Sekolah Dasar - Adelia Afriyanti Adelia Afriyanti; J.Julia; Aah Ahmad Syahid (Jurnal Elementaria Edukasia, 2023)
ABSTRACT Learning in the 21st century cannot be separated from the influence of digital technology. Learning to understand the contents of fairy tales through teachers reading fairy tales in front of the class is no longer suitable for students in the digital era. Therefore, further progress is needed in the use of learning media. Learning to understand the content of fairy tales using animated videos or audio-visual media can be an alternative method that teachers can use. Research comparing the effectiveness of using audiovisual and textual learning media to improve elementary school students' ability to understand the content of fairy tales was conducted at SDN Situraja. The research method used in this research is a quantitative method. Students' enthusiasm in learning to understand fairy tales using animated videos or audio-visual media will be better than learning to understand fairy tales in writing and reading in front of the class. This can be seen in the average ability of students to understand fairy tales. The average understanding ability of students after using learning media is 76.40, while the average ability to understand fairy tales before using it is 58.00, and the average ability of understanding students after using text media is 75.20, while the average ability students' understanding after using text media was 75.20, while the average students' understanding ability after using text media was 75.20, while the average students' understanding ability after using text media was 75.20. understanding the previous tale is 75.20. is 75.20. is 52.80. Apart from increasing students' ability to understand fairy tales at an average level, the use of animated video media also helps students become more active in the learning process. This can be seen when the teacher delivers By using 10-choice multiple choice questions before and after the broadcast, most students answered correctly the questions asked by the teacher.